PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KESEJAHTERAAN GURU, DAN DISIPLIN KERJA TERHADAP KINERJA GURU SMK DI KECAMATAN PAKEM SLEMAN (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
The study is aimed to determine a.) How much influence of the school leadership on teacher is performance, b.) How much influence of the welfare on the teacher’s performance, c.) How much influance of work discipline on teacher is performance, d.) How much influence of the principal leadership,welfare and discipline of work on teacher’s performance.This research was conducted in Vocational High School (SMK) in District Pakem ,namely SMK Muhammadiyah Pakem,SMK Sanjaya Pakem,SMK Kanisius Pakem,SMK HP I and HP II Pakem.This research applied a quantitative survey method. The population of the study was all vocational teachers in district Pakem totaling 117 respondents. This study took as many as 95 teachers as respondets with a proportional random sampling techniques. Collecting data was done using a questionnaire. Analysis of data normality,linearity and multicollinearity.The data analysis used multiple regression with three independent variables.The hypothesis testing used F-test or ANOVA at the same time,followed by hypothesis testing used individual partial test (t-test).Data Prossesing used SPSS Programme.The results showed that a.) There is a positive and significant influence of school leadership,teacher welfare and discipline work on teacher’s performance. This mean that there is an increase in teacher is performance which is determined by three factors, b.) there is a positive and significant influence of school leadership on teacher’s performance those for the better the principal’s leadership will better the performance of a teacher, c.) There is a significant positive influence on teacher’s performance there for the welfare of the teachers and the teacher will get better performance as well, d.) There is a positive and significant influence on the performance of work discilpine thus the higher the level of teacher discipline the better the performance.